Verification of The Water Transport Parameter – Moisture Storage Function of Autoclaved Aerated Concrete – Approximately Calculated from a Small Set of Measured Characteristic Values - Durica, Pavol; Vertal, Marian (Communications - Scientific letters of the University of Zilina, 2011)
The aim of the paper is to determine the moisture transport parameters for selected type of autoclaved aerated concrete using fly ash order to carry out the numerical analysis of the hygrothermal performance of selected building structures in real conditions. The moisture storage function (sorption, suction) and the liquid water transport coefficient are taken into consideration. Obtaining knowledge of these parameters involves a series of laboratory measurements and tests. Applying those parameters into modern calculation methods (WUFI) we will be able to analyse annual hygrothermal performance of porous concrete wall constructions in climatic conditions of Central Europe. This article aims to test use of a simplified approximating method to establish the moisture storage function for a chosen building material. Influences of the method on accuracy of the simulated calculation will also be analysed.